Gluten-free diet affects fecal small non-coding RNA profiles and microbiome composition in celiac disease supporting a host-gut microbiota crosstalk - Antonio Francavilla; Giulio Ferrero; Barbara Pardini; Sonia Tarallo; Laura Zanatto; Gian Paolo Caviglia; Sabina Sieri; Sara Grioni; Giulia Francescato; Francesco Stalla; Cristina Guiotto; Lucia Crocella; et al. (Gut Microbes, 2023)
ABSTRACTCurrent treatment for celiac disease (CD) is adhering to a gluten-free diet (GFD), although its long-term molecular effects are still undescribed. New molecular features detectable in stool may improve and facilitate noninvasive clinical management of CD. For this purpose, fecal small non-coding RNAs (sncRNAs) and gut microbiome profiles were concomitantly explored in CD subjects in relation to strict (or not) GFD adherence over time. In this observational study, we performed small RNA and shotgun metagenomic sequencing in stool from 63 treated CD (tCD) and 3 untreated subjects as well as 66 sex- and age-matched healthy controls. tCD included 51 individuals on strict GFD and with negative transglutaminase (TG) serology (tCD-TG-) and 12 symptomatic with not strict/short-time of GFD adherence and positive TG serology (tCD-TG+). Samples from additional 40 healthy adult individuals and a cohort of 19 untreated pediatric CD subjects and 19 sex/age matched controls were analyzed to further test the outcomes. Several miRNA and microbial profiles were altered in tCD subjects (adj. p < .05). Findings were validated in the external group of adult controls. In tCD-TG-, GFD duration correlated with five miRNA levels (p < .05): for miR-4533-3p and miR-2681-3p, the longer the diet adherence, the less the expression differed from controls. tCD-TG+ and untreated pediatric CD patients showed a similar miRNA dysregulation. Immune-response, trans-membrane transport and cell death pathways were enriched in targets of identified miRNAs. Bifidobacterium longum, Ruminococcus bicirculans, and Haemophilus parainfluenzae abundances shifted (adj. p < .05) with a progressive reduction of denitrification pathways with GFD length. Integrative analysis highlighted 121 miRNA-bacterial relationships (adj. p < .05). Specific molecular patterns in stool characterize CD subjects, reflecting either the long-term GFD effects or the gut inflammatory status, in case of a not strict/short-time adherence. Our findings suggest novel host-microbial interplays and could help the discovery of biomarkers for GFD monitoring over time.